2019
DOI: 10.3390/molecules24112057
|View full text |Cite
|
Sign up to set email alerts
|

Seed Characteristics and Nutritional Composition of Pine Nut from Five Populations of P. cembroides from the States of Hidalgo and Chihuahua, Mexico

Abstract: The aim of this study was to analyze the seed characteristics and nutritional composition of five pine nut P. cembroides samples from two Mexican states. Morphometry, proximal composition, phenolic compounds, and antioxidant capacity were determined. Samples differed in several morphometric trails, but important differences were documented between SMCH and JCZH samples from Hidalgo State. JCZH and FMH had the highest contents of water, lipids, protein, flavonoids, and antioxidant activity, while CMCC populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…As far as we know, this is the first time that the variability of fatty acid composition between populations of P. pinaster , P. halepensis and P. brutia is described. Some recent studies have shown that the chemical composition of seeds reflects the climatic conditions to which the plant was subjected, leading to differences between populations of pine species [39–41] . Our results agree with those studies because significant correlations were observed between the content of some fatty acids and certain ecologic parameters of P. halepensis populations.…”
Section: Resultssupporting
confidence: 91%
“…As far as we know, this is the first time that the variability of fatty acid composition between populations of P. pinaster , P. halepensis and P. brutia is described. Some recent studies have shown that the chemical composition of seeds reflects the climatic conditions to which the plant was subjected, leading to differences between populations of pine species [39–41] . Our results agree with those studies because significant correlations were observed between the content of some fatty acids and certain ecologic parameters of P. halepensis populations.…”
Section: Resultssupporting
confidence: 91%
“…The content of total hydrophilic phenolic compounds and flavonoids in PEC is similar to that reported in a previous study [52] but higher than those reported in the USDA Food and Nutrient Database [28] and for another Mexican PEC [23,24]. The content of total hydrophilic phenolic compounds and flavonoids in WPN and PPN, despite being lower than the other samples assayed here, seems to be higher than those reported by Valero-Galvan et al [29] for several pine nut accessions from Hidalgo and Chihuahua (Mexico). It is noteworthy that EOA had 2.2 (PEC) to 23.2 (PPN) times more hydrophilic phenolic compounds than any other sample analyzed in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Before going any further, it should be stated that peanuts are not tree nuts but legumes, but they are commercially considered as such and they are commonly included in chemical compositional studies of edible nuts. The chemical (proximate) profile of PPN was similar to several P. cembroides accessions from Hidalgo and Chihuahua, Mexico [29]. Quercus acorns from two Mediterranean species ( Q. ithaburensis, Q. calliprinos ) are rich (g 100 g −1 ) in carbohydrates (42–79) and dietary fiber (13–52) but they are moderate sources of protein (2–5), fat (0.8–3.1) and ash (1.8–3.2) [30], while acorns from Q. robur have a moisture, ash and protein content ranging from 2.0–7.9, 2.1–8.4 and 4.2–14.1, respectively [31]; such a macronutrient composition differs from that found for EOA, which, to our knowledge, has not been reported previously.…”
Section: Discussionmentioning
confidence: 95%
“…Zulfqar et al found higher TPC (77.2 ± 1.41 mg GAE/g) in methanolic extract of P. gerardiana dry nuts than in EtOAc extract (52.5 ± 2.9 mg GAE/g) [ 16 ]. Valero-Galván et al found that Pinus cembroides grown in five states of Mexico presented different amounts of TPC in the methanol seed extract [ 24 ]. Bolling et al report that TPC of pine nut was 68 mg GAE/100 mg; however, as per Phenol-Explorer database reports 58 mg GAE/100 mg [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zulfqar et al reported that the percentage of DPPH inhibition of both MeOH and EtOAc extract of P. gerardiana dry nuts was 76.33 ± 2.51% and 73.67 ± 2.75% at concentration of 10 mg/mL and was statistically insignificant [ 16 ]. Valero-Galván et al reported that methanol seed extract of P. cembroides grown in the five states of Mexico revealed different antioxidant activity assessed by DPPH assay [ 24 ]. P. halepinsis found in Palestine region displayed that methanolic extract by maceration and Soxhlet extraction method showed IC50 of 0.12 mg/mL and 0.43 mg/mL, respectively [ 10 ].…”
Section: Resultsmentioning
confidence: 99%